Planejamento estratégico: uma ferramenta de gestão para a cooperativa de agricultores familiares de Terra Alta - SANTOS, Fabio Dias dos (2018)
It is possible to understand that planning techniques have evolved to the extent that the adopted models congregate aspects that have been neglected previously, for example, the long-term planning exceeded the view of the previous model that was annual and incorporating the projection of a long- term intentions. Next, the Strategic Planning surpassed the exclusively financial aspect, starting to group the environmental factors (internal and external) that can interfere or potentiate its behavior. In the 1980s, Strategic Management sought to approximate the planning of implementation, so that the plans and strategies outlined would make reference to the management of organizations. This method of accelerated change significantly affects organizations and their management models, establishing new skills to adapt to the new context. Reflecting on how to construct a Strategic Plan in a participatory manner that meets the real needs of Coafta's family farmers? The present paper presents a possibility of change with the Strategic Planning as a Management Tool for the Cooperative of Farmers of Terra Alta, with the objective of analyzing the socioeconomic, political and management aspects of the members of the cooperative and elaborating the Strategic Planning from of participatory and methodological processes that organize Coafta in the ambit of the Solidary Economy. Therefore, based on the references of action research, the research was developed in a participatory, democratic and collective way among the various stakeholders interested in the research, supported by authors who discuss Strategic Planning and Cooperative Management. This work was planned and carried out with family farmers from the Cooperative of Terra Alta Farmers (Coafta) in the State of Pará. This work was carried out in stages that resulted in a reassessment of organizational identity and a situational diagnosis. Based on these steps, the cooperative's plan of action was built and its implementation, control and evaluation focused on solutions to problems diagnosed by family farmers associated with Coafta. It was concluded that the use of Strategic Planning as a management concept for economic solidarity projects is interesting, as long as the community is committed to the development of the same objectives